2016
DOI: 10.1177/2325967116671692
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Injections With Needle Tenotomy for Gluteus Medius Tendinopathy

Abstract: Background:Gluteal tendinopathy is a prevalent condition that can be associated with significant pain and disability. To date, no studies have prospectively assessed the efficacy of intratendinous platelet-rich plasma (PRP) injections as a minimally invasive treatment for gluteus medius tendinopathy.Purpose:To prospectively assess the efficacy of intratendinous PRP injections as treatment for chronic recalcitrant gluteus medius tendinopathy.Study Design:Case series; Level of evidence, 4.Methods:During the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 70 publications
0
38
0
1
Order By: Relevance
“…This can be explained by their analgesic effects on local neuropeptides and neurotransmitters that relay pain and not by their anti-inflammatory properties [16]. This is supported by histopathological studies that found that there is no association between gluteal tendinopathies and serious inflammations, which means that CSI cannot provide long-term pain relief [16,18]. Additionally, it was found that there is a risk of rupture if corticosteroids are injected into a tendon [12,19 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This can be explained by their analgesic effects on local neuropeptides and neurotransmitters that relay pain and not by their anti-inflammatory properties [16]. This is supported by histopathological studies that found that there is no association between gluteal tendinopathies and serious inflammations, which means that CSI cannot provide long-term pain relief [16,18]. Additionally, it was found that there is a risk of rupture if corticosteroids are injected into a tendon [12,19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CSI have been shown to provide only short-term pain relief [2,9]. This can be explained by their analgesic effects on local neuropeptides and neurotransmitters that relay pain and not by their anti-inflammatory properties [16]. This is supported by histopathological studies that found that there is no association between gluteal tendinopathies and serious inflammations, which means that CSI cannot provide long-term pain relief [16,18].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations